Focal fibrocartilaginous dysplasia in the humerus - EROL, BÜLENT (LIPPINCOTT WILLIAMS & WILKINS, 2006)
Focal fibrocartilaginous dysplasia is an uncommon, benign bone lesion that causes deformity of the long bones in young children. It has most commonly been encountered in the proximal tibia, and very rarely in the long bones of the upper limb, that is, the proximal humerus, distal radius, ulna and proximal phalanx. Only one case of focal fibrocartilaginous dysplasia of the proximal humerus has been reported previously. The present study reports two such additional cases that were diagnosed in late childhood. The clinical presentation and radiographic findings are described with an emphasis on the natural evolution of the disease. Limb-length discrepancy is anticipated in these children in the long-term follow-up and, therefore, surgical intervention should be considered in treatment. J Pediatr Orthop B 15:449-452 (C) 2006 Lippincott Williams & Wilkins.
Keywords: fibrocartilaginous dysplasia; focal; upper limb